2004
DOI: 10.1128/jb.186.7.2006-2018.2004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Butanol Stress and Tolerance in Clostridium acetobutylicum

Abstract: The effects of challenges with low (0.25%, vol/vol) and high (0.75%) concentrations of butanol on the growth, glucose metabolism, product formation, and transcriptional program of the solvent-tolerant Clostridium acetobutylicum strain 824(pGROE1) and the plasmid control strain 824(pSOS95del) were used to study solvent tolerance and stress response. Strain 824(pGROE1) was generated by groESL overexpression. The growth of 824(pGROE1) was less inhibited than that of 824(pSOS95del), and 824(pGROE1) was able to met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
175
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(194 citation statements)
references
References 62 publications
17
175
0
Order By: Relevance
“…Third, our new microarray data show consistent patterns of expression for all predicted (Paredes et al, 2004) operons, and a select set of these data are shown and discussed below. Fourth, our data display consistent temporal patterns for genes belonging to the same operon or (Alsaker et al, 2004;Tomas et al, 2004). Gray indicates that the data were not reliable.…”
Section: Validation Of Microarray Datamentioning
confidence: 71%
See 4 more Smart Citations
“…Third, our new microarray data show consistent patterns of expression for all predicted (Paredes et al, 2004) operons, and a select set of these data are shown and discussed below. Fourth, our data display consistent temporal patterns for genes belonging to the same operon or (Alsaker et al, 2004;Tomas et al, 2004). Gray indicates that the data were not reliable.…”
Section: Validation Of Microarray Datamentioning
confidence: 71%
“…The validity of the microarray data used in this study was assessed based on five different approaches/metrics. First, the new microarray data of butanol stress were compared against the earlier, partial genomic data which were obtained with recombinant C. acetobutylicum strains (Alsaker et al, 2004;Tomas et al, 2004). Second, we expected that the acetate and butyrate stress would upregulate several general stress response genes, and also, based on earlier physiological studies (Huesemann and Papoutsakis, 1986;Papoutsakis, 1988, 1990), the solvent-formation genes.…”
Section: Overview Of the Experimental Design And Strategy To Assess Dmentioning
confidence: 99%
See 3 more Smart Citations